AN ANALYSIS OF PREFIXES AND SUFFIXES IN BUNUTAN DIALECT OF BALINESE: A Descriptive Study - ., I Gusti Ayu Ngurah Shanti Ningrum; ., Prof. Dr.I Ketut Seken,MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Abstrak Penelitian ini dirancang dalam bentuk deskriptif kualitatif. Penelitian ini bertujuan untuk mendeskripsikan asal usul kata dan perubahan kata awalan dan akhiran dialek bahasa Bali Bunutan. Teknik yang digunakan adalah observasi dan wawancara. Dalam penelitian ini, terdapat tiga narasumber yang dipilih. Hasil dari penelitian ini menunjukkan terdapat tiga jenis awalan yang ditemukan di dialek Bunutan, yaitu {ma-}, {me-}, and N-, dan terdapat tiga akhiran: {-ang}, {-in}, and, {-nye} yang ditemukan di dialek bahasa Bali Bunutan. Awalan dan akhiran di dialek bahasa Bali Bunutan yang termasuk awalan asal usul kata {ma-}, {me-}, and N-, dan akhiran suffixes {-ang} dan {-in}. Awalan dan akhiran di dialek bahasa Bali Bunutan yang termasuk perubahan kata awalan N- and akhiran {-ang}, {-in}, and, {-nye}. Kata Kunci : Kata-kata kunci: awalan, akhiran, asal usul kata, perubahan kata ABSTRACT This study was designed in the form of descriptive qualitative study. This study aimed at describing the derivational and inflectional prefixes and suffixes in Bunutan Dialect of Balinese. The techniques used to collect the data were observation and interview. In this study, there were three informants chosen. The results of this study showed that there are three kinds of prefixes found in Bunutan Dialect, namely {ma-}, {me-}, and {n-} and there were three kinds of suffixes: {-ang}, {-in}, and, {-nye} which is found in Bunutan Dialect of Balinese. Prefixes and suffixes in Bunutan Dialect of Balinese which belonged to derivational were prefix {ma-}, {me-}, and {n-} and suffixes {-ang} and {-in}. Prefixes and suffixes in Bunutan Dialect of Balinese which belonged to inflection were prefix {n-} and suffix {-ang}, {-in}, and, {-nye}.Prefixes and suffixes in Bunutan Dialect of Balinese which belonged to derivational were prefix {ma-}, {me-}, and N- and suffixes {-ang} and {-in}. Prefixes and suffixes in Bunutan Dialect of Balinese which belonged to inflection were prefix N- and suffix {-ang}, {-in}, and, {-nye}. keyword : Keywords: prefixes, suffixes, derivational, inflectional